UAV Photogrammetry for Road Surface Modelling - Birutė Ruzgienė; Česlovas Aksamitauskas; Ignas Daugėla; Šarūnas Prokopimas; Virgaudas Puodžiukas; Donatas Rekus (The Baltic Journal of Road and Bridge Engineering)
Recently, the interest of Unmanned Aerial Vehicle application in photogrammetric environment for roads observation and monitoring has increased in many countries, in Lithuania as well. The experimental object for demonstration of capability and efficiency of aerial vehicle-based remote sensing technology for road data collection was a western bypass of Vilnius. The platform of the model UX5 Trimble with mounted camera Sony NEX-5R was applied for gaining images. The implemented means are mobile and not expensive. Photogrammetric technique with software package Business Center Photogrammetry Module was applied for the modelling of images. The correctness of digital surface model generally depends on camera resolution, flight height and accuracy of ground control points. The coordinates of control points were determined using Global Positioning System Trimble R4. Paper demonstrates results of a new technology application possibilities for linear object (road) mapping and accuracy evaluation of spatial models. The road points positioning accuracy investigation was carried out in consideration with geodetic control measurements. The average root mean square error for the points coordinates is 2.94 cm, and standard deviations – 2.78 cm. Analyzing coincidence or mismatches of Vilnius western bypass project data with photogrammetric product, not significant discrepancies of road section features were determined. The cost consideration of Unmanned Aerial Vehicle in conjunction with photogrammetry employment at experimental object is presented.